Pan-cancer analysis of the prognostic and immunological role of GJB2: a potential target for survival and immunotherapy - Jia, Yuting; Guo, Bin; Zhang, Wenbin; Wang, Feng; Zhang, Yong; Zhang, Quanmao; Li, Erfeng (Frontiers in Oncology, 2023)
Background: Although some studies have demonstrated that GJB2 plays an important role in the tumorigenesis and progression of certain cancers, no systematic pan-cancer analysis of GJB2 has been performed, and the prognostic and immunological value of GJB2 in pan-cancer remains to be explored. Method: The difference in GJB2 expression in different tumor tissues and adjacent normal tissues was analyzed using the TIMER, GEPIA and Sangerbox database. Then, the GEPIA database and Kaplan-Meier plotter were used to evaluate the correlation between GJB2 expression and pan-cancer prognosis. The association for GJB2 expression with human cancer immune checkpoints (ICP), tumor mutational load (TMB), microsatellite instability (MSI) and neoantigen and tumor immune cell infiltration were assayed via the Sangerbox database. The cBioPortal website was used to explore the mutation characteristics of GJB2. Moreover, we obtained GJB2-binding proteins using STRING and co-expressed genes using the GEPIA2 database. DAVID was used to explore the functions and related enrichment pathways of GJB2. Finally, we explored the role and mechanism of GJB2 in PAAD using the Linkedomics website to further validate the mechanism of GJB2 in tumorigenesis and development. Results: GJB2 gene was highly expressed in multiple tumors and has a positive or negative association with prognosis in various cancers. More importantly, GJB2 was related to TMB, MSI and neoantigen and tumor immune cell infiltration in a variety of cancers and played an instrumental role in the tumor microenvironment (TME). Furthermore, enrichment analysis revealed that the mechanism of GJB2 action in tumors mainly involves: gap junction-mediated intercellular transport, regulation of cell communication by electrical coupling, ion transmembrane transport, autocrine signaling, apoptotic signaling pathway, NOD-like receptor signaling pathway, p53 signaling pathway, PI3K-Akt signaling pathway and so on. Conclusions: Given its role in tumorigenesis and tumor immunity, GJB2 might be served as a potential prognostic biomarker and a new target for future immunotherapy of pan-cancerous tumors. Keywords: pan-cancer, prognosis, immune infiltration, alteration, immune checkpoint, tumor mutational burden, microsatellite instability, neoantigen.